Trois pièces d’échecs en ivoire de morse découvertes au château de Crèvecœur-en-Auge (Calvados) - Jean-François Goret; François Poplin (Archéologie Médiévale)
Early excavations on the Crèvecoeur-en-Auge castle site (Calvados) yielded three remarkable chess pieces comprising a king or fers, a knight and a pawn. They are made of walrus ivory and are finely decorated, displaying high-quality workmanship. Their stylised shapes are in the tradition of non-figurative Arabian pieces, copied in the West from the end of the 10th century. They have been published several times, but with only summary descriptions. This paper aims at completing the missing information. By paying particular attention to the use of this raw material, the origin and the dating of the pieces are challenged.